Perancangan Busana Casual Wanita dari Bahan Jumputan Dipadu Bahan Lurik - Titin Prihatini; Selly Mutiara Kusumasari (Jurnal Socia Akademika, 2020)
This research aims to determine the result of women's casual clothing from Jumputan combined material seen from the model indicators and colour compatibility. Methods of research using experimental methods, sensory testing and documentation. The subject of his research is 2 (two) pieces of casual fashion from the jumputan cloth combined with the Lurik. The stage of the experiment is to create design, body measurement, pattern making, cutting, sewing, and finishing. Sensory test is done against 30 panellists with sensory test sheets containing items about design suitability with the materials and motives, design lines or silhouettes, and the harmony of the colour of the jumputan fabric and striated cloth. From the sensory test results, seen in terms of models, the results of casual clothing can be said the model is suitable because it is already followingfollowing the criteria of casual fashion. In terms of colour harmony, the results of casual fashion can be said to be matched colour, because it is already following the criteria of colour harmony. Overall (total looks) of casual fashion experimental results according to casual fashion.